DEVELOPMENT OF THE MULTILEVEL TALENT MANAGEMENT MODELING FOR BUILDING TRANSFORMATIONAL LEADERSHIP CAPABILITY OF CHIEF IN WHOLESALE INDUSTRY OF THAILAND - เอื้ออารีสุขสกุล, อรุณรุ่ง; จันทึก, ธีระวัฒน์ (RMUTT Global Business and Economics Review, 2016)
This research aims to examine components in a multilevel talent management model for building transformational leadership capability of chief in the wholesale Industry of Thailand by applying documentary research technique classified by organizational and individual levels. This documentary research explored the related concepts and theories and then synthesized and summarized them into the tables. It applied the social networks concepts by using the Pajek program for the analyses of components and relationship of the multilevel talent management model for building transformational leadership capability. The results were 1) a structure casual model at the organizational level is comprised of talent management, effective team, leadership development, organizational climate, and transformational leadership and 2) a structure casual model of the individual level is comprised of personality, creativity, organizational citizenship behavior, management skills, and transformational leadership.